Kinetics of Mass Transfer, Colour, Total Polyphenol and Texture Change of Manilkara Zapota During Convective Air Drying - Chien wha Chong; Chung Lim Law; Michael Wha Cloke; Luqman Chuah Abdullah; Wan Ramli Wan Daud (ASEAN Journal of Chemical Engineering, 2009)
The effects of air temperature and product size on drying kinetics, retained total polyphenol content (TPC), hardness kinetics and total colour change (.E) kinetics of ciku (Manilkara zapota) were investigated. In addition, five terms of the theoretical model were used to estimate the effective diffusivity values during drying at temperatures from40OC to 70OC. The drying rates of dried ciku were increased with increasing temperature and decreasing product size. It was found that hardness of ciku dried at temperature higher than 60OC increased significantly, when the moisture content was reduced toless than 0.5 g H2O/g DM (dry basis). In terms of nutritional value, the retained total polyphenol content (TPC) of dried ciku in hot air drying also increasing with temperature. The highest retained TPC was 141 mg GAE/ 100g of samples, which can be obtained from drying at 70OC.